How is the Income Disparity in the Context of North Sumatera Province: A Conceptual Framework - Kesuma, Sinar Indra; Sirojuzilam, Sirojuzilam; Erlina, Erlina; Lubis, Suwardi (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The dynamics of regional income has attracted the attention of practitioners, scholars and academics. A critical issue in development for the past and current decades is the disparity or inequality of income distribution among regions. The disparity of income distribution, in this case, refers to the convergence theory of the Solow-Swan model developed by Barro and Sala-i-Martin. Accordingly, the study will identify and analyse several prepositions. The contribution of this work for the next step will provide an additional wealth of knowledge in regional economics and regional development, especially with regard to the convergence of regional income disparities. This study also will contribute to the local governments to accelerate the convergence of income disparities in the Province of North Sumatera. Later, the authors' work will provide input to local governments on the variables that converge or diverge in the process of income disparity convergence so that recommendations can be taken based on the estimated study results.